Vocabulary is important for some, but not all reading skills - Ricketts, J; Nation, K; Bishop, D (Lawrence Erlbaum Associates, Inc., 2007)
Although there is evidence for a close link between the development of oral vocabulary and reading comprehension, less clear is whether oral vocabulary skills relate to the development of word-level reading skills. This study investigated vocabulary and literacy in 81 children aged 8 to 10 years. In regression analyses, vocabulary accounted for unique variance in exception word reading and reading comprehension, but not text reading accuracy, decoding, or regular word reading. Consistent with these data, children with poor reading comprehension exhibited oral vocabulary weaknesses and read fewer exception words correctly. These finding demonstrate that oral vocabulary is associated with some, but not all, reading skills. Results are discussed in terms of current models of reading development.